Clinical Utility of Serum Lactate and Albumin in Predicting Mortality in Patients with Sepsis Admitted to the Intensive Care Unit: A Prospective Cohort Study - Benjamin Isac John; AS Sathiqali; Rohith George; B Mukhtarahmed (Journal of Clinical and Diagnostic Research)
Introduction: Sepsis is a life-threatening condition characterised by systemic inflammation and multiorgan dysfunction in response to infection. Despite the specificity of prognostic scoring systems such as Sequential Organ Failure Assessment (SOFA) and Acute Physiology And Chronic Health Evaluation II (APACHE II), their limited sensitivity and reliance on multiple laboratory parameters highlight the need for simpler, effective biomarkers. Serum albumin, a negative acute-phase reactant and lactate, an organ hypoperfusion marker, are potential biomarkers for assessing the severity of sepsis. Aim: To evaluate the prognostic significance of serial serum lactate and albumin levels, as well as their ratio, in predicting outcomes in Intensive Care Unit (ICU) patients with sepsis. Materials and Methods: This prospective cohort study was conducted in the medical ICU of Yenepoya Medical College and Hospital, Mangaluru, Karnataka, India that included 95 adults admitted to the medical ICU with suspected sepsis, meeting the Sepsis-3 criteria. Serum lactate and albumin levels were measured on days 1, 3 and 5 post-diagnosis. Patient outcomes, including mortality and duration of hospital stay, were documented. Statistical analysis was performed using Statistical Package for Social Sciences (SPSS) version 27.0, which included Pearson’s correlation to evaluate relationships between lactate and albumin levels, Student’s t-test for group comparisons and Receiver Operating Characteristic (ROC) curve analysis to assess the predictive accuracy of the Lactate/Albumin Ratio (LAR). Results: The study included 95 ICU patients with sepsis (mean age: 50.25±14.65 years; 63.16% male). Prolonged hospital stays (>15 days) were noted in 61.06% of patients, with 78.94% recovering. Survivors showed rising albumin levels (day 1: 2.82 g/dL; day 5: 3.43 g/dL) and declining lactate levels (day 1: 2.77 mmol/L; day 5: 1.27 mmol/L), while non survivors exhibited minimal increases in albumin (day 1: 2.87 g/dL; day 5: 3.05 g/dL) and persistently elevated lactate levels (day 1: 3.02 mmol/L; day 5: 3.35 mmol/L). On day 5, survivors had significantly higher albumin levels and lower lactate levels than non survivors. The LAR declined in survivors (day 1: 1.07; day 5: 0.54) and demonstrated marked predictive accuracy for mortality on day 5 (AUC=0.81, sensitivity=68%, specificity=95%), with diagnostic accuracy peaking at 89.21%. Conclusion: The day 5 LAR is a strong predictor of mortality in ICU patients with sepsis. The inverse correlation between lactate and albumin levels underscores their utility for early risk stratification and management of sepsis.